Gut stem cell necroptosis by genome instability triggers bowel inflammation - Wang, Ruicong; Li, Hongda; Wu, Jianfeng; Cai, Zhi-Yu; Li, Baizhou; Ni, Hengxiao; Qiu, Xingfeng; Chen, Hui; Liu, Wei; Yang, Zhang-Hua; Liu, Min; Hu, Jin; et al. (Nature (London), 2020)
The aetiology of inflammatory bowel disease (IBD) is a multifactorial interplay between heredity and environment 1 , 2 . Here we report that deficiency in SETDB1, a histone methyltransferase that mediates the trimethylation of histone H3 at lysine 9, participates in the pathogenesis of IBD. We found that levels of SETDB1 are decreased in patients with IBD, and that mice with reduced SETDB1 in intestinal stem cells developed spontaneous terminal ileitis and colitis. SETDB1 safeguards genome stability 3 , and the loss of SETDB1 in intestinal stem cells released repression of endogenous retroviruses (retrovirus-like elements with long repeats that, in humans, comprise approximately 8% of the genome). Excessive viral mimicry generated by motivated endogenous retroviruses triggered Z-DNA-binding protein 1 (ZBP1)-dependent necroptosis, which irreversibly disrupted homeostasis of the epithelial barrier and promoted bowel inflammation. Genome instability, reactive endogenous retroviruses, upregulation of ZBP1 and necroptosis were all seen in patients with IBD. Pharmaceutical inhibition of RIP3 showed a curative effect in SETDB1-deficient mice, which suggests that targeting necroptosis of intestinal stem cells may represent an approach for the treatment of severe IBD. In mouse models of bowel inflammation, depletion of the SETDB1 histone methyltransferase leads to genome instability, which releases repression of endogenous retroviruses that triggers ZBP1-dependent necroptosis and inflammation in gut.